Urinary incontinence and urinary tract infections in octogenarian women - Bjornsdottir, L T; Geirsson, R T; Jonsson, P V (Acta Obstetricia et Gynecologica Scandinavica, 2009)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: Urinary incontinence and urinary tract infection are common problems among elderly women due to age-related changes in the urogenital tract, but information regarding prevalence and presentation among the aged is limited. METHODS: A total of 97 randomly selected women aged 80-89 years, 47 living in homes for the elderly and 50 living at home, were asked about urogenital complaints in a structured interview. Medical records provided information about urinary tract infections and the use of estrogens. RESULTS: Urinary incontinence affected 46%; half of them daily. Urge incontinence was most common (43%), then mixed incontinence (28%) and stress incontinence (26%). Urge and mixed incontinence caused significantly more discomfort than stress incontinence. During the past two years 33% of the women had experienced urinary tract infection and 11% had > or = 5 infections. A total of 22 women were receiving estrogen treatment, more often in homes for the elderly (p < 0.001). Paradoxically, these women had a higher prevalence of urinary incontinence, urinary tract infection, and other complaints than women not receiving estrogens. Considerable or great discomfort from the urogenital tract was reported by 23% of the women. A third of the women had discussed urogenital complaints with a physician. CONCLUSION: In view of the prevalence of urogenital complaints, it is likely that more elderly women could benefit from early medical assessment and treatment. Indications for estrogen treatment need to be more clearly defined.